Adrenoleucodystrophy: neurophysiological aspects. Issue 9 (September 1981) - Battaglia, A; Harden, A; Pampiglione, G; Walsh, P J
Abstract : Neurophysiological investigations (EEG, ERG, VEP) were carried out in 14 boys with adrenoleucodystrophy, and in two siblings with adrenocortical deficiency, but without neurological symptoms. Irregular large amplitude (200-800 microvolts) slow activity was found in the EEG of all adrenoleucodystrophy patients, usually more prominent over the posterior regions of the brain. No short duration spikes or complex wave were seen in any of the EEGs, even in those patients who had had seizures. Clinical deterioration was not always accompanied by an increase in EEG abnormalities. The ERG was of usual amplitude and wave form, while the VEP (flash) was altered in four cases. The two clinically unaffected siblings had normal ERG/VEP, and only a modest excess of slow waves in the EEG. The neurophysiological findings in adrenoleucodystrophy are not seen in other diseases with similar clinical symptoms in the same age group.